2023
DOI: 10.1109/access.2023.3244780
|View full text |Cite
|
Sign up to set email alerts
|

Algebra of L-Banded Matrices

Abstract: Convergence is a crucial issue in iterative algorithms. Damping is commonly employed to ensure the convergence of iterative algorithms. The conventional ways of damping are scalar-wise, and either heuristic or empirical. Recently, an analytically optimized vector damping was proposed for memory message-passing (iterative) algorithms. As a result, it yields a special class of covariance matrices called L-banded matrices. In this paper, we show these matrices have broad algebraic properties arising from their L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…We take lightweight age estimation as an example. In [42], several standard CNNs are proposed for the task of age estimation. However, the model sizes of these standard CNNs are too large to be lightweight.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We take lightweight age estimation as an example. In [42], several standard CNNs are proposed for the task of age estimation. However, the model sizes of these standard CNNs are too large to be lightweight.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…However, the model sizes of these standard CNNs are too large to be lightweight. In [42], the authors suggested to replace the standard convolutions of these standard CNNs by the separable convolutions in order to significantly reduce the number of parameters. Nevertheless, the prediction accuracy of their constructed lightweight CNN based on separable convolutions is not preserved compared to the standard CNN.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing techniques have been recognized as an effective strategy to construct hydrogel actuators with excellent performance. [219][220][221][222][223] Jeremy Odent et al [215] demonstrated a family of multiresponsive hydrogel-based actuators via SLA 3D printing (Figure 7A). Through three separate synthetic strategies [172] B) Printed round-sheet, zero, negative Poisson's ratio structure, and honeycomb planar structure.…”
Section: Soft Actuatorsmentioning
confidence: 99%
“…3,4 It offers several advantages over conventional imaging techniques in the sensing and analysis of objects in challenging environments. [5][6][7] Thus far, multiband polarization imaging technique is ideal for a variety of polarization-based applications, such as medical diagnosis with tissue assessment and cytometry imaging, 8 the measurement of aerosol density in the atmosphere, 9 and the geological exploration of glacier and vegetation distribution. 10 As one of the competitive candidates, multiband polarization-sensitive photodetection shows great potential for multiband polarization imaging, which is capable of detecting both the intensity and polarization state of light.…”
Section: Introductionmentioning
confidence: 99%